Insufficient birth weight incidence and risk factors at Tacna Hipolito Unanue Hospital 2001 – 2010 - Ticona Rendón, Manuel (2013)
Objectives: To determine frequency and perinatal outcomes of underweight newborns at Tacna Hipolito Unanue Hospital. Design: Retrospective, epidemiological case-control. Setting: Hospital Hipolito Unanue of Tacna, Peru. Population: We analyzed data of 3 622 live births in singleton pregnancies weighing 2 500 to 2 999 g, born during years 2001 to 2010, compared with 24 556 controls 3 000 to 3 999 g. Interventions: Bivariate analysis, using OR with 95% confidence intervals. Perinatal Data System was used. Main outcome measures: Characteristics and perinatal outcomes. Results: The frequency of underweight newborns was 10,77 x 100 live births, with downward trend during the ten years. Low birth weight was associated with female sex, prematurity, depression at one minute and five minutes after birth. Adverse perinatal outcomes were higher morbidity (OR=1,54) and neonatal mortality (OR=4,54); risk conditions were intrauterine growth retardation (OR=25,5), metabolic disorders (OR=3,01), respiratory distress syndrome (OR=2,8), sepsis (OR=2,76), congenital malformations (OR=2.57), hyperbilirubinemia (OR=2) and perinatal asphyxia (OR=1,65). Conclusions: The underweight newborn at Tacna Hipolito Unanue Hospital was at high risk of neonatal morbidity and mortality.